Fox is coming! - Patterson, James, 1947-; Kulka, Joe (New York : Little, Brown and Company, 2024)
The chicks on the farm are in a hurried race to hide away as Fox gives chase.
Ages 3-5.
Keywords: Stories in rhyme; Foxes -- Fiction; Animals -- Infancy -- Fiction; Chickens -- Fiction; Stories in rhyme; Picture books